As modinhas de Raimundo Ramos nas encruzilhadas do tempo: canção popular e ensino de história - Homci, Isick Kauê Bianchini (2024)
In the History teaching research here materialized , modinhas seresteiras’ songs were used, among other productions by Raimundo Ramos, also known as “Ramos Cotôco” - an astute bohemian and a cultural mediator from Ceará. His songs were admitted after considering musical language specificities, as narratives that configure partially refractory antidisciplinary practices against the modernity projects that attemped to be imposed in Brazil between the two last decades in the 19th century and the first decade in the 20th century. Composed in the intertice between 1888 and 1906, these poems and “modinhas” striked diverse themes related to everyday life in Fortaleza City such as race, fashion, behavior ,urban remodel, social control, bohemia, migrations and so on. In the developed teaching experiment in basic education, Ramos’ poetry and songs were analyzed using references such as Bell Hooks, Lélia Gonzales and Frantz Fanon, in orther to discuss the patriarchal and racist country formation, structured since Brazil’s colonization, and its current face molding that was benig generated through modernity projects settled in the sanitation thinking and social current darwinism in the transition period from monarchy and slaveholder period to the republican system grounded by free salaried work. In the meantime, these songs were used during the class as a teaching resource, historical source, and artistic product, starting from elaborated discussions by José Geraldo Vinci de Moraes, Marcos Napolitano, Miriam Hermeto, Kátia Abud, José D’Asssunção Barros and Olavo Soares, among others. As reference there were history teaching researchers, such as Isabel Barca, Maria Auxiliadora Schmidt and Peter Lee. The results obtained through this teaching experiment performed at Arquiteto Rogério Froes Elementary and High School,with 3rd year high school students enabled the creation, as a didatic product, of a teaching sequency based on a workshop, and having as a central axis the analysis of “modinhas seresteiras” by Raimundo Ramos